2007
DOI: 10.1063/1.2768347
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast excited-state dynamics of tetraphenylethylene studied by semiclassical simulation

Abstract: Detailed simulation study is reported for the excited-state dynamics of photoisomerization of cis-tetraphenylethylene (TPE) following excitation by a femtosecond laser pulse. The technique for this investigation is semiclassical dynamics simulation, which is described briefly in the paper. Upon photoexcitation by a femtosecond laser pulse, the stretching motion of the ethylenic bond of TPE is initially excited, leading to a significant lengthening of ethylenic bond in 300 fs. Twisting motion about the ethyleni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
87
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 54 publications
5
87
1
Order By: Relevance
“…Therefore, the nature of hydrogen bond in solution is of particular interest and has been investigated extensively by various experimental and theoretical methods, since solute-solvent interactions play a fundamental role in molecular nonequilibrium processes in liquids [11][12][13][14][15][16][17][18][19][20][21][22][23]. However, little is known about electronic excited-state hydrogen bond.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the nature of hydrogen bond in solution is of particular interest and has been investigated extensively by various experimental and theoretical methods, since solute-solvent interactions play a fundamental role in molecular nonequilibrium processes in liquids [11][12][13][14][15][16][17][18][19][20][21][22][23]. However, little is known about electronic excited-state hydrogen bond.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Dihydrogen bonding can influence the structure, reactivity, and selectivity of compounds in the gas and condensed phase. [11][12][13][14] Particularly, both experimental and theoretical studies have shown that two interacting hydrogen atoms in a dihydrogen bond could escape as H 2 . [15][16][17][18][19][20] Thus, dihydrogen bond can be viewed as a precursor to dehydrogenation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Femtosecond laser technology has been widely applied in the fields of physics and chemistry [1][2][3][4]. In the past decade, a number of interesting phenomena in the intense femtosecond laser field, such as above threshold ionization (ATI) [5,6], AC-Stark shift [7][8][9], harmonic generation [10,11], coherent phenomena [12,13], and laser-induced continuum structure [14], have been reported.…”
Section: Introductionmentioning
confidence: 99%